Observed changes in precipitation extremes across 11 basins in China during 1961–2013. (9th October 2015) - Wu, Xushu; Wang, Zhaoli; Zhou, Xiaowen; Lai, Chengguang; Lin, Wenxin; Chen, Xiaohong
ABSTRACT: Extremes of weather and climate can cause disasters such as floods and droughts. Further studies of precipitation extremes are crucial for enabling reliable projections of future changes. In this study, we used a high‐resolution (0.5° × 0.5°) gridded precipitation data set to analyse these events across the 11 basins in China between 1961 and 2013 mainly by the Mann–Kendall and generalized extreme value methods. Our results indicated a wetter trend in the Tarim River Basin (TRB) but drier conditions in the central Yangtze River Basin (YRB), western Pearl River Basin and eastern Yarlung Tsangpo River Basin. There was an increasing risk of flooding in the mid‐lower YRB and Minjiang River Basin (MRB), and an increasing risk of drought in the central Lantsang River Basin. The results revealed strengthened maximum 1‐day precipitation (RX1DAY) in the Liaohe River Basin (LB), YRB, MRB and TRB, together with strengthened maximum 5‐day precipitation (RX5DAY) in the Songhua River Basin, MRB and TRB during 1987–2013. RX1DAY and RX5DAY for return periods of 20 and 50 years gradually decreased from southeast to northwest. Along the south‐eastern coastline of the Mainland and on Hainan Island, the RX1DAY for the 20‐ and 50‐year return periods would exceed 165 and 195 mm, respectively, whereas the RX5DAY would exceed 270 and 320 mm for the same return periods. Furthermore, summer Southern Oscillation Index (SOI) positively impacted precipitation extremes in the Yellow River Basin and YRB, and autumn SOI negatively impacted the extremes of the next year in LB and YRB, while winter SOI negatively impacted the extremes of the next year in YRB. Additionally, the East Asia summer monsoon (EASM) and the South Asia summer monsoon (SASM) were both associated with precipitation extremes across China; however, EASM contributed more to these events than did the SASM.